سلطة الانزياح وجمالية الخروج في القصيدة الجزائرية المعاصرة قراءة في شعر يوسف وغليسي وعاشور فني –أنموذجا - حساين, رابح محمد (جامعة الوادي - University of Eloued, 2023)
إنّ سلطة الانزياح في نصوص الشعر الجزائري تتمظهر من خلال الاختراق الشّعري لبنى اللغة والخروج عن المألوف، وكذا التّحطيم البنائي في جسد القصيدة الجزائرية المعاصرة، هذه الأخيرة أضحت بسبب ذلك تمارس استفزازا دلاليا على القارئ، ممّا تدفع به إلى إنتاج الدّلالة بعد أن يجمع هذا القارئ شظايا دوالـها المنكسرة. وهذا ما دفع بنا من خلال هذه الدراسة إلى الوقوف على النّصوص الشّعرية لكلّ من عاشور فني ويوسف وغليسي رغبةً منا في الكشف بالتحليل والبحث العميق عن سلطة الانزياح وجمالية الخروج في مدوّنتيْهما الشّعرية، وعن كيفية تجسّد مظاهر وأشكال الانزياح في لغتهما وداخل نصوصهما الفنّية، ممّا يدّل ذلك على نضج التّجربة الفنية لدى كلّ من الشاعريْن. The power of displacement in the texts of Algerian poetry is demonstrated by the poetic penetration of the structures of language and out of the ordinary, as well as the structural destruction in the body of the contemporary Algerian poem, the latter becoming a semantic provocation to the reader, which leads him to produce significance after this reader collects fragments of her broken functions. This prompted us through this study to identify the poetic texts of Ashour Fani, Youssef waghlissi in order to reveal the analysis and the deep search for the power of displacement and the aesthetics of going out in their poetry blogs, and how to embody the manifestations and forms of displacement in their language and within their artistic texts, indicating the maturity of the artistic experience of each of the poets. ا
Article
Keywords: سلطة الانزياح ; الشعر الجزائري ; عاشور فني ; يوسف وغليسي ; القصيدة الجزائرية; Displacement Authority ; Algerian Poetry ; Ashur Fenni ; Youssef